The octadecaneuropeptide ODN protects astrocytes against hydrogen peroxide-induced apoptosis via a PKA/MAPK-dependent mechanism. - Yosra Hamdi (Public Library of Science (PLoS), 2012)
Astrocytes synthesize and release endozepines, a family of regulatory peptides, including the octadecaneuropeptide (ODN) an endogenous ligand of both central-type benzodiazepine (CBR) and metabotropic receptors. We have recently shown that ODN exerts a protective effect against hydrogen peroxide (H(2)O(2))-induced oxidative stress in astrocytes. The purpose of the present study was to determine the type of receptor and the transduction pathways involved in the protective effect of ODN in cultured rat astrocytes. We have first observed a protective activity of ODN at very low concentrations that was abrogated by the metabotropic ODN receptor antagonist cyclo(1-8)[DLeu(5)]OP, but not by the CBR antagonist flumazenil. We have also found that the metabotropic ODN receptor is positively coupled to adenylyl cyclase in astrocytes and that the glioprotective action of ODN upon H(2)O(2)-induced astrocyte death is PKA- and MEK-dependent, but PLC/PKC-independent. Downstream of PKA, ODN induced ERK phosphorylation, which in turn activated the expression of the anti-apoptotic gene Bcl-2 and blocked the stimulation by H(2)O(2) of the pro-apoptotic gene Bax. The effect of ODN on the Bax/Bcl-2 balance contributed to abolish the deleterious action of H(2)O(2) on mitochondrial membrane integrity and caspase-3 activation. Finally, the inhibitory effect of ODN on caspase-3 activity was shown to be PKA and MEK-dependent. In conclusion, the present results demonstrate that the potent glioprotective action of ODN against oxidative stress involves the metabotropic ODN receptor coupled to the PKA/ERK-kinase pathway to inhibit caspase-3 activation.